AUTHENTIC ASSESSMENT IN ACTION: ENGLISH TEACHERS’ PERCEPTION AND PRACTICES FOR ASSESSING STUDENTS’ PRODUCTIVE SKILLS AT SENIOR HIGH SCHOOL - Eka Setiawati, Ni Luh; Era Marsakawati, Ni Putu; Ramendra, Dewa Putu (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2024)
This study explores how English teachers’ perceptions and practices of authentic assessment for assessing students’ productive skills at Senior High School 2 Kuta. Using Qualitative research aims to explore in-depth information on various responses. This research is the result of expressing a person's various thoughts about a topic (McCarthy, 2017). The result revealed teachers believe that the design and implementation of authentic assessments are critical for effectively improving students' productive skills and that these assessments should fit with the Merdeka Curriculum's learning objectives. Teachers acknowledge that authentic assessments have a beneficial impact on student's ability to apply skills in real-life circumstances, and they emphasize the importance of planning and implementation in achieving good assessment outcomes.